A meta‐analysis of the effects of acute alcohol intoxication on witness recall. Issue 3 (4th March 2019) - Jores, Theo; Colloff, Melissa F.; Kloft, Lilian; Smailes, Harriet; Flowe, Heather D.
Summary: There is widespread belief in the legal system that alcohol impairs witness testimony. Nevertheless, most laboratory studies examining the effects of alcohol on witness testimony suggest that alcohol may affect the number of correct but not incorrect details recalled. However, it is difficult to draw conclusions because sample sizes, testing paradigms, and recall measures vary between individual studies. We conducted a meta‐analysis to address this issue. We found alcohol intoxication had a significant and moderate sized effect on the number of correct details recalled ( g  = 0.40). The effect of alcohol on the number of incorrect details recalled was not significant. Further, the effect of alcohol on the recall of correct details was significantly moderated by multiple factors like intoxication level, the retention interval length between encoding and recall, and the types of questions asked (i.e., free recall vs. cued recall). We discuss the applied implications of the results.